Association of Angiogenesis Gene Expression With Cancer Prognosis and Immunotherapy Efficacy - Li, Xin-yu; Ma, Wei-Ning; Su, Li-xin; Shen, Yuchen; Zhang, Liming; Shao, Yuhao; Wang, Deming; Wang, Zhenfeng; Wen, Ming-Zhe; Yang, Xi-tao (Frontiers in Cell and Developmental Biology, 2022)
Background: A large number of new blood vessels are formed during the process of tumour development. These new blood vessels provide nutrients and water for tumour growth, while spreading tumour cells to distant areas and forming new metastases in different parts of the body. Evidence suggests that tumour angiogenesis is closely associated with the tumour microenvironment, and is regulated by a variety of pro-angiogenic factors and/or angiogenic inhibitors. Methods: Herein, we performed a comprehensive characterization of angiogenesis genes expression in a pan-cancer manner involving 33 cancer types. The study used gene expression data from several databases and immune checkpoint blockade-treated patient cohorts. An angiogenesis score was assigned to The Cancer Genome Atlas (TCGA) pan-cancer data, with one angiogenesis score per sample for each tumour. Results: It was found that the angiogenesis genes vary widely across cancer types, and are associated with a number of genomic and immunological features. Macrophages and iTreg infiltration were generally higher in tumours with high angiogenesis scores, but lymphocytes and B cells showed the opposite trend. Notably, NK cells showed significantly different correlations among cancer types. Furthermore, results showed that a high angiogenesis score was associated with poor survival in the majority of cancer types. Conclusion：This study shows that the expression of angiogenesis genes is an important feature of tumour biology that has significant impact on patient prognosis.